3D laparoscopy as a tertiary cytoreductive (TCR) surgery in infiltrating ureter recurrent epithelial ovarian cancer – case report and a mini-review of the literature - Szopiński, Tomasz; Mor, Igal; Okoń, Krzysztof; Baranowski, Włodzimierz; Jerzak, Małgorzata (Menopause Review/Przegląd Menopauzalny, 2018)
The paper describes a case of a 61-year-old woman with recurrent epithelial ovarian cancer infiltrating the ureter treated with 3D laparoscopy as a tertiary cytoreductive surgery (TCR). In addition, a mini-review of the literature concerning TCR is presented.